Effect of supervised versus self-directed exercise and dietary practices on body weight and glycaemic control with individuals having type 2 diabetes - Alemmebrat Kiflu Adane (Turkish Journal of Kinesiology, 2019)
Similar to a highly developed country, these days the rapid and parallel increase in sedentary lifestyle and type 2 diabetes (T2DM) is becoming one of the major public health concerns of Ethiopia. Despite the fact that pharmacological medicines are mostly ordered by physicians as a treatment modality to T2DM, regular physical exercise and healthy diet habits are not well understood and practiced throughout society. Previous studies also documented that the latter two approaches are the two key management tools for diabetes and it assists in preventing diabetes-related health complications, insulin resistance, and T2DM. The present study examined the difference in body weight and fasting plasma glucose (FPG) improvement in 16 moderately overweight male individuals having T2DM for 10wks intervention, to this end experimental with retrospective cohort study design was used. After qualified, the recruitment criteria subjects were randomly categorized into two groups, i.e. experimental (n = 8) and control (n = 8).  Individuals who have received a supervised exercise program and close dietary advice were compared with those who were engaged in self-directed exercise and also have their own eating habits over the study program.   To analysis, the data, dependent t-test and Pearson's correlation were used. In all cases, the statistical significance threshold was P < 0.05. At the end of the intervention, significant bodyweight reduction and FPG improvement were observed in the experimental group as compared to their counterparts. Therefore, it was concluded that professionally supervised regular exercise with a close dietary practice should be the main choice of individuals having T2DM in order to manage and achieve sustainable body weight control and FPG for better health and treatment modalities.